PHARMACOTHERAPEUTIC POTENTIAL OF AVICENNIA OFFICINALIS LEAF EXTRACT IN MANAGING ALCOHOL-INDUCED HEPATOTOXICITY - Mahalakshmi S; Tehseen Javed; Kannan; Subha S C; Ruby (The Bioscan, 2025)
This study evaluates the hepatoprotective and antioxidant potential of ethanolic leaf extract of Avicenniaofficinalis in a rat model of alcohol-induced liver toxicity. Chronic ethanol administration resulted in elevated serum hepatic enzymes (SGOT, SGPT, ALP, GGT), total bilirubin, and lipid peroxidation, along with decreased levels of total protein and both enzymatic (SOD, CAT, GPx, GST) and non-enzymatic (GSH, vitamins C and E) antioxidants. Oral administration of A. officinalis extract (100 mg/kg body weight) significantly restored liver function biomarkers and antioxidant levels, comparable to the standard hepatoprotective drug silymarin. Phytochemical analysis confirmed the presence of flavonoids, alkaloids, tannins, terpenoids, and other bioactive compounds, which may contribute to its therapeutic efficacy. These findings support the potential of A. officinalis as a natural, pharmacologically active agent for the prevention and treatment of alcohol-induced hepatic damage.